Burden of visual impairment associated with eye diseases: exploratory survey of 298 Chinese patients. Issue 9 (12th September 2019) - Guan, Xiaodong; Fu, Mengyuan; Lin, Fanghui; Zhu, Dawei; Vuillermin, Daniel; Shi, Luwen
Abstract : Objectives: To explore the economic burden, prevalence of catastrophic healthcare expenditure (CHE) and the quality of life (QoL) of Chinese patients with visual impairment (VI) associated with eye diseases. Design: A questionnaire survey from March to May 2016 by structured face-to-face interviews of patients with VI. Participants: 302 patients who were diagnosed with moderate VI or worse in both eyes (visual acuity <6/18) were included, and 298 patients (98.7%) who completed the survey questionnaires were eligible for the study. Outcome measures: The economic burden was estimated by calculating participants' direct costs covered in 2015 and the definition of CHE was out-of-pocket (OOP) costs exceeding 30% of annual household income. QoL was weighed by health utility value using time-trade-off valuation techniques. Results: Annual average direct costs per patient caused by VI were US$6988.6±US$10 834.3,  and 70.3% were direct medical costs of which only 26.9% were reimbursable by medical insurance. 32.2% of households that suffered from CHE, in particular, were less wealthy patients with VI living in rural areas and without medical insurance. The health utility value was rated at 0.65 on average, and patients with VI aged 51–57, living alone and insured by commercial medical insurance had relatively less QoL. Conclusion: Our study explored the economic burden and QoL of VI associated with patients with eye diseases in China, indicating a substantial economic burden and poor QoL. Preferential medical insurance policies should be designed in relation to people with VI to further reduce the health inequalities, avoid CHE and promote QoL.